Media engineering in marine diatom Phaeodactylum tricornutum employing cost‐effective substrates for sustainable production of high‐value renewables. Issue 10 (15th June 2022) - Rehmanji, Mohammed; Nesamma, Asha Arumugam; Khan, Nida Jamil; Fatma, Tasneem; Jutur, Pannaga Pavan
Abstract: Phaeodactylum tricornutum is a marine diatom, rich in omega‐3 polyunsaturated fatty acids especially eicosapentaenoic acid (EPA) and brown pigment, that is, fucoxanthin. These high‐value renewables (HVRs) have a high commercial and nutritional relevance. In this study, our focus was to enhance the productivities of such renewables by employing media engineering strategy via., photoautotrophic (P1, P2, P3) and mixotrophic (M1, M2, M3, M4) modes of cultivation with varying substrate combinations of carbon (glycerol: 0.1 m) and nitrogen (urea: 441 mm and/or sodium nitrate: 882 mm ). Our results demonstrate that mixotrophic [M4] condition supplemented with glycerol (0.1 m ) and urea (441 mm ) feed enhanced productivities (mg L −1  day −1 ) as follows: biomass (770.0), total proteins (36.0), total lipids (22.0), total carbohydrates (23.0) with fatty acid methyl esters (9.6), EPA (2.7), and fucoxanthin (1.1), respectively. The overall yield of EPA represents 28% of total fatty acids in the mixotrophic [M4] condition. In conclusion, our improved strategy of feeding urea to a glycerol‐supplemented medium defines a new efficient biomass valorization paradigm with cost‐effective substrates for the production of HVRs in oleaginous diatoms P. tricornutum . Graphical Abstract and Lay Summary: Our findings define a new approach of low‐cost microalgal high‐value renewables (HVRs) production and a roadmap for synthesis of brown‐pigment "fucoxanthin" coproduced with omega fatty acids from oleaginous diatom P. tricornutum .